Higher Muscle Damage Triggered by Shorter Inter-Set Rest Periods in Volume-Equated Resistance Exercise - Senna, Gilmar Weber; Dantas, Estélio Henrique Martin; Scudese, Estevão; Brandão, Paula Paraguassú; Lira, Vitor A.; Baffi, Matheus; Ribeiro, Luiz Claudio Pereira; Simão, Roberto; Thomas, Ewan; Bianco, Antonino (Frontiers in Physiology, 2022)
Objectives: The aim of the manuscript was to analyze the effects of two rest periods between volume-equated resistance exercise (RE) on inflammatory responses (cytokines and leukocyte) and muscle damage. Methods: Ten trained men (26.40 ± 4.73 years, 80.71 ± 8.95 kg, 176.03 ± 6.11 cm) voluntarily participated in training sessions consisting of 5 sets of 10 reps performed at 10-RM on 1) the barbell bench press followed by 2) leg press, with either 1- or 3-minute rest between sets and exercises. Circulating concentrations of different biomarkers were measured before (Pre), and after 3h (excepted for cytokines), 6h, 12h, and 24h from exercise. The rate of perceived exertion (RPE) was recorded after each set on both planned visits. Results: We found greater increases triggered by the 1-minute rest period in Creatine Kinase (CK), occurring from 12h to 24h post-exercise compared to the 3-minute rest condition. A significant increase in the 1-minute rest condition was also observed in the total number of leukocytes, neutrophils, and monocytes. The 1-minute rest period also triggered increases compared to baseline in pro-inflammatory cytokines (Interleukin 1 beta (IL-1β), p = 0.004; Tumor necrosis factor α (TNF-α), p = 0.01; granulocyte-macrophage colony-stimulating factor (GM-CSF), p = 0.01), which were more evident after 6h and 12h post-exercise. Similarly, increases in anti-inflammatory cytokines (Interleukin 5 (IL-5), p= 0.01; Interleukin 6 (IL-6), p=0.01; Interleukin 10 (IL-10), p=0.01) at all time-points were oserved. Conclusions: Our results indicate that a 1-minute rest condition in volume equated RE promoted greater overall muscle tissue damage with a longer duration of the inflammatory processes compared to a 3-minute rest.